The Role of Emotional Intelligence and Self-Efficacy in Enhancing Employee Performance: A Systematic Literature Review - Aziz, Muhammad Fikri Nur; Mahmud, Renaldi; Hidayati, Retno; Lataruva, Eisha (Research Horizon, 2024)
This study investigates the role of Emotional Intelligence (EI) and Self-Efficacy in enhancing employee performance, framed within the context of an empowered economy for sustainable prosperity in Indonesia. As businesses increasingly recognize the importance of non-technical competencies in driving success, Emotional Intelligence has emerged as a critical factor in employee productivity and satisfaction. Self-Efficacy, as an individual's belief in their ability to succeed, has been identified as a crucial mediator in the relationship between EI and performance outcomes. This paper presents a Systematic Literature Review (SLR) that synthesizes research findings on the impact of Emotional Intelligence and Self-Efficacy on employee performance. By examining recent studies, the review highlights how these constructs contribute to sustainable workplace practices and foster a culture of empowerment. Findings reveal that EI positively influences performance by enhancing employees' adaptability, resilience, and collaboration skills, with Self-Efficacy serving as a significant mediator in these relationships. This review underscores the importance of incorporating Emotional Intelligence and Self- Efficacy into human resource strategies to support sustainable economic growth and organizational success.